2017
DOI: 10.46538/hlj.14.3.4
|View full text |Cite
|
Sign up to set email alerts
|

Metalinguistic Intuitions and Dominant Language Transfer in Heritage Spanish Syllabification

Abstract: While heritage speakers of Spanish have been shown to differ from monolingual speakers along many morphosyntactic lines, comparatively few studies in heritage linguistics have focused on phonology. To test whether the knowledge of English phonotactics would influence Spanish-English heritage speaker syllabification patterns in Spanish, 29 heritage and 29 monolingual speakers of Spanish completed a paper-and-pencil syllabification task in which they divided 80 Spanish words into syllables. Stimuli were controll… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

1
1
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 21 publications
1
1
0
Order By: Relevance
“…One of the most important aims of the present study was to measure the correlation between metalinguistic awareness and language dominance in the case of bilingual learners in the Saudi context. This study renews the finding of previous studies on language dominance (Cokely, 2012;Robinson Anthony et al, 2020;Shelton et al, 2017). According to Robinson et al (2020) metalinguistic transfer has been demonstrated to be associated with patterns of language dominance in the same way as studies of lexical processing have been.…”
Section: Relationshipsupporting
confidence: 89%
See 1 more Smart Citation
“…One of the most important aims of the present study was to measure the correlation between metalinguistic awareness and language dominance in the case of bilingual learners in the Saudi context. This study renews the finding of previous studies on language dominance (Cokely, 2012;Robinson Anthony et al, 2020;Shelton et al, 2017). According to Robinson et al (2020) metalinguistic transfer has been demonstrated to be associated with patterns of language dominance in the same way as studies of lexical processing have been.…”
Section: Relationshipsupporting
confidence: 89%
“…In summary, the participants indicate that extremely young multilingual youngsters are capable of accurately reporting their language skills. Additionally, a study by Shelton et al (2017) determined if bilingual Spanish speakers and monolingual Spanish speakers behave differently while syllabifying words in their native language. The findings of a syllabification exercise indicate that the phonotactic patterns of a (societally) dominant language can have an effect on metalinguistic intuitions about syllabification in the heritage language.…”
Section: Relationshipmentioning
confidence: 99%